Novel scheme towards interfacial charge transfer between ZnIn2S4 and BiOBr for efficient photocatalytic removal of organics and chromium (VI) from water. (September 2022) - He, Zuming; Yang, Hanpei; Sunarso, Jaka; Wong, Ngie Hing; Huang, Zhengyi; Xia, Yongmei; Wang, Yong; Su, Jiangbin; Wang, Lina; Kang, Li
Abstract: Construction of Z-scheme heterostructure is an effective strategy to enhance the charge carriers' separation. However, successfully achieving this on the defect heterojunction to improve the photocatalytic activity remains challenging. This work successfully obtained sulfur vacancy in the ZnIn2 S4 /BiOBr (SZIS/BOB) heterojunction composites with S–O covalent bonding using a hydrothermal method. As a result, they exhibited superior photocatalytic and stability performance. The optimized SZIS/BOB-10 exhibited excellent rhodamine B degradation (95.2%) and chromium (VI) reduction (97.8%) within 100 min under visible light. The enhanced composites with S-vacancies, S–O bond, and internal electric field induced the Z-scheme charge transfer mechanism. We had verified this mechanism based on the surface photovoltage spectra, electron spin response spectra, and density functional theory calculations. This work not only provides valuable insights into designing photocatalysts with a direct Z scheme heterostructure but also delineates a promising strategy for developing efficient photocatalysts to degrade organic pollutants. Graphical abstract: Schematic illustration of the possible photoelectron generation and transport routes in the SZIS/BOB heterostructure. Also, the photocatalytic reaction mechanism for RhB degradation and Cr(VI) reduction under visible light irradiation. Image 1 Highlights: Constructing surface defect ZnIn2 S4 /BiOBr heterojunction. The S–O covalent bond was found in the ZnIn2 S4 /BiOBr heterojunction interface. The S–O bond boosting interfacial charge transfer in ZnIn2 S4 /BiOBr heterojunction. ZnIn2 S4 /BiOBr exhibited outstanding photocatalytic performance under visible light.